The Smile Index: Part 3. A Simple, Prognostic Severity Scale for Unilateral Cleft Palate. Issue 10 (22nd October 2021) - Yao, Caroline A.; Vartanian, Emma D.; Nagengast, Eric; McCullough, Meghan; Auslander, Allyn; Magee, William P.
Abstract : Background: Unilateral cleft palates have a large spectrum of variability. Key morphologic factors such as cleft width and palatal length are not represented in current classification systems. Palate length and velopharyngeal port size are clinically linked to speech outcomes, as the soft palate must close the posterior pharynx for proper phonation. This study investigates the relationship between objective preoperative measures and postoperative velopharyngeal port size, to define a reproducible severity scale. Methods: Surgical data were prospectively collected from unilateral cleft palate patients in Morocco, Bolivia, Vietnam, and Madagascar. Key measurements were cleft width and palate width at the hard–soft palate junction, alveolar cleft width, vertical alveolar discrepancy, velopharyngeal port size. Cleft width ratio (CWR) was defined as the width of the cleft at the hard–soft junction, divided by the palate width. Results: Seventy-six patients were evaluated. Thirty-one had complete clefts and average age at surgical repair was 2.9 years. Mean CWR was 0.50 ± 0.12. Palate length was increased by an average of 2.2 mm (11%) after palatoplasty. Multivariate analysis determined greater CWR and larger preoperative velopharyngeal ports were significantly correlated with a smaller percent change in palate length after palatoplasty ( P < 0.01). Conclusions: A wider palatal cleft decreases the surgeon's ability to decrease velopharyngeal port size through palatoplasty. Given the ease of measurement even in low-resource settings, CWR may be a valuable tool for setting expectations for speech results, modifying surgical technique, and correlating future speech outcomes in evidence-based cleft care.